SARS-CoV-2 infection in cancer patients on active therapy after the booster dose of mRNA vaccines. (August 2022) - Di Giacomo, Anna M.; Giacobini, Gianluca; Anichini, Gabriele; Gandolfo, Claudia; D'alonzo, Vincenzo; Calabrò, Luana; Lofiego, Maria F.; Cusi, Maria G.; Maio, Michele
Abstract: Introduction: The protective role against SARS-CoV-2 infection by the third booster dose of mRNA vaccines in cancer patients with solid malignancies is presently unknown. We prospectively investigated the occurrence of COVID-19 in cancer patients on active therapy after the booster vaccine dose. Methods: Cancer patients on treatment at the Center for Immuno-Oncology (CIO) of the University Hospital of Siena, Italy, and health care workers at CIO who had received a booster third dose of mRNA vaccine entered a systematic follow-up monitoring period to prospectively assess their potential risk of SARS-CoV-2 infection. Serological and microneutralization assay were utilized to assess levels of anti-spike IgG, and of neutralizing antibodies to the SARS-CoV-2 Wild Type, Delta and Omicron variants, respectively, after the booster dose and after negativization of the nasopharyngeal swab for those who had developed COVID-19. Results: Ninety cancer patients with solid tumors on active treatment (Cohort 1) and 30 health care workers (Cohort 2) underwent a booster third dose of mRNA vaccine. After the booster dose, the median value of anti-spike IgG was higher (p = 0.009) in patients than in healthy subjects. Remarkably, 11/90 (12%) patients and 11/30 (37%) healthy subjects tested positive to SARS-CoV-2 infection during the monitoring period. Similar levels of anti-spike IgG and of neutralizing antibodies against all the investigated variants, with geometric mean titers of neutralizing antibodies against the Omicron being the lowest were detected after the booster dose and after COVID-19 in both Cohorts. Conclusions: The occurrence of SARS-CoV-2 infection we observed in a sizable proportion of booster-dosed cancer patients and in healthy subjects during the Omicron outbreak indicates that highly specific vaccines against SARS-CoV-2 variants are urgently required. Highlights: Patients with solid tumours on active therapy received the third dose of mRNA vaccine to SARS-CoV-2. Anti-spike and neutralising Ig increased equally in patients and healthy subjects. COVID-19 risk was prospectively assessed during the Omicron outbreak. High rates of COVID-19 occurred in booster-dosed patients and healthy subjects. More specific vaccines for SARS-CoV-2 variants are urgently required.